All-terrain vehicle use related fracture rates, patterns, and associations from 2002 to 2015 in the USA. Issue 2 (February 2019) - Richards, Jarod A.; Loder, Randall T.
Highlights: Over 1.8 million ED visits and 482, 501 (25.9%) fractures for ATV-related injuries across the U.S. from 2002 to 2015. Fractures involved the extremities in over 75% of patients. Upper extremity fractures accounted for over 50% of all fractures. The mean age of those with fractures was 27.5 years. The admission rate was 28.5%. Abstract: Background: Since their introduction to USA markets in the late 20 th century, all-terrain vehicles (ATVs) have been a significant source of trauma. Many paediatric studies have demonstrated the disproportionate rate in which minors are affected by ATV-related trauma, but no studies have been performed on a large sample size spanning all age and geographic ranges. This study is the first to analyze ATV-related fracture rates, patterns, and associated risks across all ages nationwide. Methods & statistical analysis: The National Electronic Injury Surveillance System (NEISS) was queried for ATV-related trauma for the years 2002–2015. The data were analyzed by age, sex, race, alcohol usage, helmet usage, type of injury, fracture location, and disposition from the emergency department (ED). Continuous data were analyzed using the t -test (2 groups) or ANOVA (≥3 groups). Discrete data were analyzed using χ 2 tests. SUDAAN 10™ software was used to account for the stratified and weighted nature of the data. Significance was set at p  < 0.05. Results: There were an estimated 1, 862, 342 ED visits for ATV-related injuries from 2002 to 2015; 482, 501 (25.9%) sustained fractures with a mean age of 27.5 years. Among those with fractures, 75.7% were male, 28.5% resulted in hospital admission, 43.9% occurred at home, and 57.5% were unhelmeted. Anatomically, 51.8% involved the upper extremity, 23.6% involved the lower extremity, 6.4% involved the spine, 8.5% involved the skull/face, and 9.7% involved the ribs/sternum. Alcohol use was most frequently associated with skull (13.2%) and cervical spine (13.0%) fractures. Patients with skull or facial fractures were unhelmeted 88% of the time, and 87% of skull fractures were associated with brain injury. ATV-related fractures peaked in 2007 at 44, 283 and trended downward through 2014. Conclusion: This study is the first of its kind to analyze ATV-related trauma over all age groups throughout the entire USA. It can serve as a reference for clinical decision-making and future studies. It also reinforces the need for ATV regulation advocacy, specifically helmet use.